The racial discourse and the Dutch Reformed Church: looking through a descriptive-empirical lens ... towards a normative task - W. J. Schoeman (Acta Theologica)
The discourse between the Dutch Reformed Church (DRC) and race is a difficult and intense one. The aim of this article is to give a descriptive-empirical description of the relationship between the DRC and race by using the Church Mirror surveys. An altered social distance scale is used to measure church acceptance. In the discourse on race, acceptance and unity in the DRC with regard to racial prejudice and attitudes towards the “other” group have a stronger voice than theological or religious arguments. As a normative task in this discourse, at least two aspects can be pointed out: developing a framework for forgiveness and a confession on racism.